ANALISIS PENGARUH LOCUS OF CONTROL DAN PERILAKU DISFUNGSIONAL AUDITOR TERHADAP KUALITAS AUDIT - Haniar Putri (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2020)
This research has purpose to examine the influence of locus of control, premature sign-off, and underreporting of time toward the quality of audit. Populations of this research are the entire active auditor in public accountant company in Surabaya. Technique of sampling in this research uses random sampling. Method of Collecting Data done by questionnaire. Total amount of Data from this research is 100 questionnaires.The result of hypothesis test indicates that: 1) Locus of Control has significant influence on the quality of audit; 2) Premature Sign Off has significant and positive influence on the quality of audit; 3) Underreporting of Time does not have significant influence on the quality of audit